Peran Komunikasi Interpersonal Siswa Kelas XI Pasca Toxic Friendship Dalam Bersosialisasi (Studi Deskriptif Kualitatif Siswa Kelas XI Pasca Toxic Friendship Dalam Bersosialisasi Di SMAN 12 Padang) - Sania Fadhilla Syerin Nim; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This research aims to analyze the role of interpersonal communication in helping class XI high school students at SMA N 12 Padang to return to socializing after experiencing Toxic Friendship. Toxic Friendship is an unhealthy friendship, which is characterized by manipulation, betrayal, excessive jealousy towards friends, and unhealthy competition. This research uses a qualitative approach with descriptive methods and in-depth interviews to understand students' experiences, communication patterns and adaptation strategies in overcoming the psychological and social impacts of facing Toxic Friendship. The research results show that students who have experienced toxic friendships tend to experience emotional obstacles, such as lack of self-confidence, excessive anxiety in friendships and social isolation. However, interpersonal communication skills, such as self- reflection, developing empathy, and openness to felt emotions, as well as building self- confidence, will be able to help the recovery process after experiencing a bad friendship.